1996
DOI: 10.1063/1.472102
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of large-scale multi-configuration self-consistent field wave functions by expectation values of local operators

Abstract: Articles you may be interested inThe multi-configuration self-consistent field method within a polarizable embedded framework J. Chem. Phys. 139, 044101 (2013); 10.1063/1.4811835Approximately extensive modifications of the multireference configuration interaction method: A theoretical and practical analysis Large multiconfiguration selfconsistentfield wave functions for the ozone moleculeWe have developed a method to analyze multi-configuration self-consistent field wave functions for open-shell systems, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
1
23
1
Order By: Relevance
“…These are spinor and spatial constraints, respectively. The MOs of the ROHF state 11 B 1u are taken as starting orbitals for the CASSCF calculations, which means that the ten 3d-like orbitals build up the active space. Since these orbitals belong to the onedimensional irreps a g , a g , b 1u , b 1u , b 1g , a u , b 2u , b 3g , b 3u , and b 2g , the ferromagnetic Sϭ5 state belongs to irrep B 1u .…”
Section: B the Active-electron Approach Using Casscfmentioning
confidence: 99%
See 2 more Smart Citations
“…These are spinor and spatial constraints, respectively. The MOs of the ROHF state 11 B 1u are taken as starting orbitals for the CASSCF calculations, which means that the ten 3d-like orbitals build up the active space. Since these orbitals belong to the onedimensional irreps a g , a g , b 1u , b 1u , b 1g , a u , b 2u , b 3g , b 3u , and b 2g , the ferromagnetic Sϭ5 state belongs to irrep B 1u .…”
Section: B the Active-electron Approach Using Casscfmentioning
confidence: 99%
“…Therefore, we analyze the CASSCF wave functions for all six multiplet states Sϭ0,1,...,5 by calculating expectation values for local operators. This method for an analysis of MCSCF wave functions, which is based on localized molecular orbitals, has already been presented in more detailed in previous work by Mödl et al, 11 so we only give here a short summary of the concept. The MOs of all six CASSCF states are subjected to a Foster-Boys localization procedure.…”
Section: B the Active-electron Approach Using Casscfmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] This decomposition was performed by calculating expectation values over local operators. [24] We computed for a definite Y AO m s by means of a formula which accounts for the non-orthogonality of the AO determinants. [25] A rapid process for computing such weights has been suggested and applied.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that CASSCF energy di↵erences usually provide a good approximation to the experimental spin state ordering but it is also demonstrated that the values of the magnetic coupling constants are normally too small [316,317]. The active space used for the study is the minimal one, with 8 electrons and 8 orbitals (Mn-3d 5 and Cr-3d 3 ).…”
Section: The Robustness Of the Spin Hamiltonianmentioning
confidence: 99%